2016
DOI: 10.1088/0953-2048/29/4/044003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the quench propagation in a 1.5 T MgB2MRI magnet design with varied wire compositions

Abstract: To reduce the usage of liquid helium in MRI magnets, magnesium diboride (MgB2), a high temperature superconductor, has been considered for use in a design of conduction cooled MRI magnets. Compared to NbTi wires the normal zone propagation velocity (NZPV) in MgB2 is much slower leading to a higher temperature rise and the necessity of active quench protection. The temperature rise, resistive voltage, and NZPV during a quench in a 1.5 T main magnet design with MgB2 superconducting wire was calculated for a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…The amount of superconducting material can be reduced (compared to 1st generation wire), allowing more space to increase the percentage of copper in wire. A recent study has shown that increasing the copper fraction helps reducing the peak temperature of hot spot during quench [39]. The 2nd generation wire also allows for a higher operating temperature, which reduces the demands on the conduction cooling system [25].…”
Section: Magnetic Designmentioning
confidence: 99%
See 4 more Smart Citations
“…The amount of superconducting material can be reduced (compared to 1st generation wire), allowing more space to increase the percentage of copper in wire. A recent study has shown that increasing the copper fraction helps reducing the peak temperature of hot spot during quench [39]. The 2nd generation wire also allows for a higher operating temperature, which reduces the demands on the conduction cooling system [25].…”
Section: Magnetic Designmentioning
confidence: 99%
“…Also, once a quench begins in NbTi magnets it spreads rapidly with the NZPV being roughly in the range of 10–50 m s −1 [1]. In contrast, the MQE for a MgB 2 superconducting magnet can be as large as several Joules, which is orders of magnitude larger than the MQE for NbTi magnets [39]. The NZPV can be in the range 5–80 cm s −1 which is orders of magnitude slower than in NbTi magnets [1].…”
Section: Thermal Properties and Quench Propagation Of Mgb2 Coilsmentioning
confidence: 99%
See 3 more Smart Citations